2010
DOI: 10.1016/j.molbiopara.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Schistosoma japonicum schistosomules with vesicular stomatitis virus glycoprotein pseudotyped murine leukemia retrovirus and expression of reporter human telomerase reverse transcriptase in the transgenic schistosomes

Abstract: Although draft genome sequences of two of the major human schistosomes, Schistosoma japonicum and S. mansoni are available, the structures and characteristics of most genes and the influence of exogenous genes on the metabolism of schistosomes remain uncharacterized. Furthermore, which functional genomics approaches will be tractable for schistosomes are not yet apparent. Here, the vesicular stomatitis virus glycoprotein (VSVG)-pseudotyped pantropic retroviral vector pBABE-puro was modified to incorporate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Studies in schistosomes identify the use of pseudotyped retroviral vectors as another approach to DNA transformation (Yang et al 2010; Rinaldi et al 2012; Hagen et al 2015). It is likely that the success of approach stems to a significant degree from the susceptibility of the schistosome tegument to invasion by the pseudotyped retroviruses and that the same caveats as discussed for electroporation will apply in the application of this approach to parasitic nematodes.…”
Section: Future Directionsmentioning
confidence: 99%
“…Studies in schistosomes identify the use of pseudotyped retroviral vectors as another approach to DNA transformation (Yang et al 2010; Rinaldi et al 2012; Hagen et al 2015). It is likely that the success of approach stems to a significant degree from the susceptibility of the schistosome tegument to invasion by the pseudotyped retroviruses and that the same caveats as discussed for electroporation will apply in the application of this approach to parasitic nematodes.…”
Section: Future Directionsmentioning
confidence: 99%
“…Both vector-based RNAi and expression of foreign transgenes have begun to be deployed in studies with schistosomes, with potential outcomes including validation of putative vaccine candidates and even the overexpression of candidate antigens. Pseudotyped murine leukemia virus and the piggyBac transposon have both been shown to transduce developmental stages of schistosomes, leading to chromosomal integration of retroviral transgenes and transgene reporter activity Morales et al, 2007;Yang et al, 2010). Moreover, a vector-based RNAi approach has been reported in which the MLV transgene encoded a long hairpin RNA specific for a schistosome protease involved in hemoglobinolysis (Tchoubrieva et al 2010).…”
Section: Schistosomesmentioning
confidence: 99%
“…We have shown that vesicular stomatitis virus glycoprotein pseudotyped murine leukemia virus (VSVG-MLV) virions can transduce different developmental stages of S. mansoni including adult worms, schistosomules and eggs, leading to integration of reporter proviral transgenes into schistosome chromosomes (Kines et al 2008; Kines et al 2010; Rinaldi et al 2011). Moreover, VSVG-MLV has recently shown utility in vector based RNA interference in adult schistosomes (Tchoubrieva et al 2010) and for expression of oncogenes in larval blood flukes (Yang et al 2010). Indeed, although other approaches are also in development for functional genomics of parasitic helminths (Dvorak et al 2010; Lok 2009; Morales et al 2007), pseudotyped MLV appears more well advanced at this time.…”
Section: Introductionmentioning
confidence: 99%